How were science mapping tools applied? the application of science mapping tools in LIS and non‐LIS domains. Issue 1 (18th October 2019) - He, Jiangen; Lou, Wen; Li, Kai
ABSTRACT: As a scientific field, scientific mapping offers a set of standardized methods and tools that can be consistently adopted by researchers in different knowledge domains to answer their own research questions. This study examined scientific articles that applied science mapping tools (SMTs) to analyze scientific domains and the citations of these application articles. To understand the roles of these application articles in scholarly communication, we analyzed them and their citations by classifying them into library and information science (LIS) and other fields (non‐LIS) in terms of both publication venues and analyzed domains. Through our preliminary study, we found that science mapping, a topic that is deeply situated in the LIS field, has gained increasing attention from various non‐LIS scientific fields over the past few years. The application articles within and outside of the LIS fields played different roles in advancing the application of science mapping.